2022
DOI: 10.1088/1757-899x/1234/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arecoline, aqueous and methanolic areca nut extracts on rumen fluke

Abstract: Paramphistomosis is a parasitic disease that causes a reduction of livestock production and economic losses worldwide. In order to avoid side effect and chemical residue from usage of chemical drugs, medicinal plant is an alternative drug for treatment. Areaca nut (Areaca catechu) which one of the domestic plants in Southeast Asia had antihelmintic activity. In this study, arecoline, aqueous and methanolic extracts of areca nut prepared in solutions were tested for antihelmintic activity against rumen flukes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…These texts record various medicinal combinations involving AN, demonstrating its efficacy in treating conditions such as oppressive sensations in the chest, heartache, lower back pain, urinary and bowel irregularities, intestinal parasitism, athlete’s foot, and oral ulcers. Subsequent scholarly investigations into the pharmacological properties of AN extracts have revealed their antidepressant, antimicrobial, anti-aging, insecticidal, anti-osteoporotic, hepatoprotective, and anti-inflammatory effects ( Dar et al, 1997 ; Lee and Choi, 1999 ; Pithayanukul et al, 2009 ; Li et al, 2017 ; Jam et al, 2021 ; Sharaf et al, 2021 ; Kweon et al, 2022 ; Puyathorn et al, 2022 ). In a recent study, extracts from arecae semen demonstrated inhibitory effects on snake venom ( More et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These texts record various medicinal combinations involving AN, demonstrating its efficacy in treating conditions such as oppressive sensations in the chest, heartache, lower back pain, urinary and bowel irregularities, intestinal parasitism, athlete’s foot, and oral ulcers. Subsequent scholarly investigations into the pharmacological properties of AN extracts have revealed their antidepressant, antimicrobial, anti-aging, insecticidal, anti-osteoporotic, hepatoprotective, and anti-inflammatory effects ( Dar et al, 1997 ; Lee and Choi, 1999 ; Pithayanukul et al, 2009 ; Li et al, 2017 ; Jam et al, 2021 ; Sharaf et al, 2021 ; Kweon et al, 2022 ; Puyathorn et al, 2022 ). In a recent study, extracts from arecae semen demonstrated inhibitory effects on snake venom ( More et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids present in AN have exhibited significant anthelminthic effects against various endoparasites in the body, such as hydatid worms, tapeworms, and acute Toxoplasma gondii parasites ( Batham, 1946 ; Zheng et al, 1998 ; Xu, 2018 ). In a study conducted by Puyathorn et al (2022) , the methanol and water crude extracts from AN, as well as the arecoline hydrobromide solution, were capable of damaging the tegument (surface membrane) of flukes and effectively eliminating them in the early stages.…”
Section: Alkaloidmentioning
confidence: 99%